Numerical modeling and experimental verification of time-dependent phase change in foodstuff - Kocatürk, Çağrı. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Time-dependent phase change in beef is modeled numerically and the results are verified experimentally. The thermal properties of beef significantly change with temperature and unlike for a pure material, the phase change occurs in a certain temperature range. Therefore, they are expressed as a function of temperature. The apparent heat capacity method is used as the phase-change model. The specific heat and the thermal conductivity of beef are measured with differential scanning calorimetry and heat flow meter, respectively. People typically cover beef with a stretch film before they put it in a freezer compartment. Hence to simulate user behavior, and also to reduce complexity mass transfer between cooling air and the beef is neglected. Since cooling air considerably impacts the freezing, it is included in the simulations. A refrigerator is utilized in both the simulations and the experiments. Its cooling system is updated so as to determine the effect of air velocity, circulation system and shelf design on the phase change process of beef. The influence of three different fan speed, two alternative blowing methods and three discrete shelf designs are investigated. A comparison of results of simulations and experiments in terms of temperature distribution and freezing time, shows that the numerical results are in agreement with the experimental measurements. As it is expected, the freezing time of beef decreases, while the fan speed is increased. The results show that more optimum freezing process could be obtained by increasing conduction heat transfer rate with the shelf design even if air flow rate is not increased. Moreover, it is observed that the top blowing method leads to a more uniform temperature gradient in beef during the freezing process.
Keywords: Food -- Effect of heat on.